Russian military operation in Ukraine: analysis from the perspective of International Law - Muhammad Nur; Galih Bagas Soesilo (Universitas Muhammadiyah Magelang, 2022)
The Russian government emphatically stated that it started a full official attack on Ukrainian territory on February 24, 2022. While, the President of Ukraine, Volodymyr Zelenskyy, declared the imposition of martial law in all regions of his country after Russia carried out a full attack. In addition, several countries in the world responded through open statements of their respective heads of state, and some were accompanied by the imposition of sanctions. Regardless of the reasons and justifications for a decision, the community is the most affected party. This war situation, of course, needs to heed the principles of humanitarian law and humanitarian principles. This paper describes how the war between Russia and Ukraine is seen from the perspective of international law and obligations of the parties under international humanitarian law. This type of research is normative juridical research. The data collecting method used is literature study. The tools used in this research are secondary data in the form of documents consisting of primary legal materials, secondary legal materials, and non-legal materials. These data were analyzed qualitatively and then presented descriptively. The results of this study found that the justifications used by the Russian government in carrying out military operations in Ukraine, namely self-defense, collective self-defense, and humanitarian intervention cannot be justified under international law. The conflict between Russia and Ukraine is included in an international armed conflict so that in order to protect civilians and certain subjects and objects, the parties to the conflict must comply with the provisions of international humanitarian law.